On-line monitoring of power transformers. A critical review of temperature sensors, oil moisture and dissolved gases - Salamanca, Santiago (2021)
Power transformers are one of the most important assets that make up electrical networks. When one of these assets has a sudden failure that involves the suspension of electricity supply to consumption centers, it can have critical consequences for the power system. Most of these types of transformer failures are related to high levels of temperature, moisture or deterioration of its insulation system. Due to the above, during the last decades online monitoring systems for power transformers have been acquiring greater relevance and integration to electrical networks and substations. In this work, a critical review of three of the most important online sensors for the operation and functioning of the transformer is carried out, such as: temperature, oil moisture and dissolved gases. Initially, an introduction is made regarding the importance of the power transformer and the concept of online monitoring. Then, a brief description is presented with the main historical milestones of these sensors as well as some of their general technical aspects. In addition, some comparison and selection criteria are proposed, citing examples and statistical cases of interest. Finally, the conclusions and recommendations of the study are presented.